Theory-based predictors of prescribing behaviour for neurodegenerative diseases: A cross-sectional survey with European healthcare professionals - Emma Begley; Jason Michael Thomas; William Hind; Carl Senior (PLoS ONE, 2026)
Objectives Explore the likelihood of healthcare professionals (HCPs) prescribing a new, novel or different to usual medication to patients with a newly diagnosed early onset or advanced stage neurodegenerative disease (ND), and identification of the theoretical behavioural determinants that underpin these predictors. Design A quantitative cross-sectional study using a newly developed survey underpinned by the Theoretical Domains Framework (TDF) was delivered online between September 2023 and March 2024. Setting All levels of healthcare where medication is prescribed for NDs across Austria, France, Germany, Italy, the Netherlands, Spain, Sweden and the UK. Participants Recruited predominately via a participation panel, HCPs who have prescribed medication for a ND in the past 2 years were eligible to take part, with 279 participants (66% male) completing the study in full. Primary and secondary outcome measures The primary outcome was HCPs’ likelihood of prescribing a new, novel or different to usual medication compared with their routine choice for patients with a newly diagnosed early onset or advanced stage ND. A secondary outcome was to identify factors aligned to the TDF that influenced prescribing and describe them using the Capability, Opportunity and Motivation – Behaviour (COM-B) model. Results HCPs were significantly more likely to consider prescribing outside of routine habit for patients with advanced stage ND compared to patients with new early onset diagnosis (60.8% [95% confidence interval (CI) 57.70, 63.95] vs 51.8% [95% CI 48.61, 55.05], respectively). Logistic regression models revealed a total of four factors that predicted prescribing. In the scenario with newly diagnosed patients, HCP intention (β = 0.324, 95% CI 4.75, 10.69), behavioural regulation (β = 0.191, 95% CI 1.57, 8.92), and social/professional role and identity (β = ‑0.184, 95% CI 1.57, 8.92) were each significant predictors of prescribing. In the scenario with patients with advanced stage ND, HCP intention also predicted prescribing (β = 0.234, 95% CI 31.02, 65.15), along with HCP belief about consequences (β = −0.145, 95% CI 2.73, 8.11). Thus, the TDF determinants that predicted prescribing indicate that COM-B capability (TDF behavioural regulation) and motivation (TDF intention, social/professional role and identity, and belief about consequences) domains may be relevant targets for changing prescribing habits. Conclusions There is a complex interplay of specific and generic predictors that influence prescribing for patients with a newly diagnosed early onset or advanced stage ND. Appropriate behaviour change frameworks that target HCPs’ capability and motivation should be considered to support changes towards the optimal use of new, novel or different to usual medication in the future.